Pine sawdust immobilized zeolitic imidazolate framework-67 derived magnetic composites: An efficient and recycable adsorbent for norfloxacin removal - Yu Zheng; Qing Shen; Jie Gao; Tian Liang; Xiao-Bing Han; Yuan Zhao; Tao Chen (Journal of Saudi Chemical Society)
Antibiotic contamination is a global environmental problem. The emerging contaminant norfloxacin (NOR) may increase the risk of drug resistance and thereby harm human health. The practical application of metal–organic framework crystals is usually limited by their powder form and difficulty in recovery. In this study, a magnetic Co-MPS-800 composite was prepared from carbonization with ZIF-67@pine sawdust, and significantly raised the NOR removing ability from wastewater. The changes in functional group composition, elemental contents, morphology, thermal stability and adsorption mechanism of the magnetic Co-MPS-800 composite were interpreted using FT-IR, XRD, SEM, BET, TGA and XPS. The Co-MPS-800 has an isoelectric point of 9.15 and a large specific surface area (174.58 m2·g−1). The impacts of pH, contact time, temperature and dosage on the performance of Co-MPS-800 were also studied. The adsorption capacity over NOR reached 221.98 mg·g−1 at 303 K, pH=6.0. The NOR adsorption is best suited a pseudo-2nd-order kinetic model and the Freundlich isotherm. Co-MPS-800 also had excellent reusability, and the removal rate reached 82.94 % after four repeated uses. Therefore, the magnetic Co-MPS-800 composite is effective in removing NOR from aqueous solutions. Altogether, this functional MOF-derived porous carbon may serve as a promising pollutant biosorbent, and its preparation strategy may provide insights for future studies.